P.062 Does the intensity of brain parenchymal contrast staining on post-recanalization dual energy head CT (DECT) of stroke patients predict the fate of brain tissue?. (November 2021) - Alomran, B; Byrne, D; Walsh, J; Murray, N; Settecase, F; Rohr, B; Rohr, A
Abstract : Background: On DECT, the ratio of maximum iodine concentration within parenchyma compared to the superior sagittal sinus has been shown to predict hemorrhagic transformation. We aimed to determine if this ratio also predicts the development of an infarct. Methods: 53 patients with small infarct cores (ASPECTS≥7) and good endovascular recanalization (mTICI 2b/3) were enrolled. Maximum brain parenchymal iodine concentration as per DECT relative to the superior sagittal sinus (iodine ratio) was correlated with the development of an infarct on follow up CT. Results: All patients showed contrast staining, 52 developed infarcts in the area of staining. The extent of infarction (smaller, equal or larger than area of staining) did not correlate with the iodine ratio. Conclusions: Brain parenchyma with contrast staining on post-procedure head CT almost invariably goes on to infarct, however the extent of infarct development is not predicted by the intensity of contrast staining. n=53 patients with successful recanalization of anterior circulation LVO infarct (TICI2b, 3) with post procedural parenchymal iodine staining There was no correlation between the degree of contrast staining on initial post procedural CT as expressed in iodine ratio and F/U infarct extent.